THE DIFFERENT PRINCIPLES ON TEACHING VOCABULARY - Djalilov Ma’rufjon Mirtimurovich (Web of Journals Publishing, 2023)
This article deals with the various principles of teaching vocabulary for different groups of learners of foreign languages.
Keywords: vocabulary, principles, general, specialized, materials, teaching.